IITA hosts Chinese delegation: strengthening global partnerships - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this video, we delve into the exciting partnership between IITA and over 17 CEOs and businessmen from China. Discover how they are working together to transform agriculture by scaling innovations in key crops like cassava and banana. Join us as we explore the potential impact of these collaborations on farming practices and food security. Don't miss out on this insightful discussion about the future of agriculture!